Evaluation Of Network Access Restrictions Using Mac Address Filtering On Microtik To Improve Network Security - Suhadin, Suhadin (Riviera Publishing, 2022)
Freedom in the use of the internet network needs to be implemented in a security system in order to keep the hotspot / wifi facilities used by responsible users. Ibnu khaldun Vocational School 1 is a state school that has many study programs, one of which is Computer and Network Engineering. The problem that occurs in the Vocational High School Ibnu Khaldun is the absence of restrictions on internet network access in the use of internet networks at schools so that students, teachers, and school staff are free to use hotspot / wifi facilities, in terms of WLAN (Wireless Local Area Network) network security. The purpose of this study is to evaluate internet network security using Mac Address Filtering which is implemented at SMK Ibnu Khaldun by registering Mac Address clients on the Access List menu to obtain access permissions in an effort to improve network security. The research approach used in this research is the quantitative approach. The result of this research is that after the Wilcoxcon test, the value of Asymp.Sig is obtained. (2-tailed) of 0.000 which indicates that the value of Asymp.Sig. (2-tailed) < 0.05 then Ha is accepted and Ho is rejected. So the results of the evaluation of internet network access restrictions using MAC Address Filtering to improve network security are accepted